(untitled) (NAU Journal of Technology and Vocational Education, 2025)
The study examined customer creation, employee proactiveness and business survival in competitive market environment of Lagos State, Nigeria. Three hypotheses were tested in this study. The descriptive research design of survey was used. The population of the study comprised 11,463 Businesses (SMEs) who have employees of 5-55 and registered with the Small and Medium Enterprises Development Agency of Nigeria (SMEDAN). The sample size is 386 businesses using Taro Yamene formula. The study used researchers self-developed instrument title: Customer’s Creation, Employee Proactiveness and Businesses Survival Questionnaire (CCEPNSQ) with reliability coefficient (r = .93) for data collection. Inferential statistics of Pearson Product Moment Correlation (PPMC) was used for testing hypotheses 1 and 2 while hypothesis 3 was tested using multiple regression analysis. The findings of the study showed that there was positive significant relationship between customer’s creation (r = 0.317, p <. 05), employee proactiveness (r = 0.210, p < .05) and businesses survival in competitive market environment of Lagos State. There was a significant composite contribution of customers creation and employee proactiveness on businesses survival in competitive market environment of Lagos State (R = 0.84, p < .05) and that about 78% variation in businesses survival in competitive market environment was accounted for by explanatory variables (customers creation and employee proactiveness). It was recommended that businesses in Lagos State and country at large should intensify efforts towards creating customers for their brand through advertisement, high quality of goods and services produces to the market. Organization should adopt participative decision-making systems, whereby employees’ demands are satisfied and promotion of work-balance should be provided.